Analisis Kesulitan Siswa dalam Pemecahan Masalah Fisika pada Konsep Medan Magnet Menggunakan Metode Krulik-Rudnick: Studi Empiris di SMAN 1 Seunagan - Sari, Mimi Vita; Afrida, Juniar; Rusydi, Rusydi; Alaidin, Samsul Fala (Desultanah: Journal Education and Social Science, 2024)
Learning difficulties often arise during the educational process, characterized by specific barriers that hinder the achievement of optimal learning outcomes. One common challenge is problem-solving, particularly in physics, which requires a systematic approach to facilitate resolution. The Krulik-Rudnick method is an effective strategy for problem-solving in physics education. This study aims to analyze the difficulties encountered by students in solving physics problems related to magnetic fields at SMAN 1 Seunagan by applying the Krulik-Rudnick theory. A qualitative research method with a descriptive design was employed in this study. The instruments used included essay tests consisting of five questions and interviews. The results revealed that students faced no significant difficulties during the first stage, which involved reading and understanding the problem. However, at the second stage of exploration and planning, only one student managed to successfully complete the task. Similarly, at the third stage of strategy selection, only one student was able to identify the correct approach. In the fourth stage, which involved finding the solution, two students managed to solve the problem correctly. Finally, in the reflection and development stage, only one student was able to complete the entire set of problems adequately